Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Sejarah Kebudayaan Islam Untuk Fase E di MAN Model 1 Plus Keterampilan Manado - Gina Nurvina Darise; Indah Wahyuni Darise (IAIN Manado, 2023)
Implementation of Independent Learning Curriculum in Islamic Cultural History subjects for phase E at MAN Model 1 Plus Keterampilan Manado. This study aims to examine the implementation of the Independent Learning Curriculum in Islamic Cultural History subjects for Phase E at MAN Model 1 Plus Keterampilan Manado which consists of planning, implementation, and learning assessment. By using descriptive qualitative research methods and data collection techniques in the form of observation, interviews, and documentation, it was found that in implementing the independent curriculum in the subjects of Islamic Cultural History for lesson planning, teachers in charge of these subjects first carry out diagnostic assessments and formulate lesson plans, namely by compiling teaching modules based on learning objectives (TP) and learning objectives flow (ATP), while the implementation of learning is carried out using project-based learning models. Learning assessments are carried out using formative assessments and summative assessments.